Practical and user friendly tool of analytic hierarchy process for decision making - Hasan Basari, Abd Samad; Hussin, Burairah; Shibghatullah, Abdul Samad (2009)
This paper discusses on the use of analytic hierarchy process (AHP) aiming at improving and enhancing the decision making process. Currently, the decision provided by user is referring to their opinion and experience. If there is a supported tool, normally mean for expert users or researchers. By using a practical and user friendly AHP tool, many users are benefited from the tool. There are three basic features of AHP called criteria, sub-criteria and alternative. These features consist of a combination of users experience and mathematical approach. The method aim to give users a decision making process according to the given problem. The results will suggest users on what is the best decision should be made. In order to test its applicability, a real world case study at Palm Oil Mill (POM) plant is used. A satisfactory result has confirmed the practicality and user friendliness of the tool.